MEN1/Menin regulates milk protein synthesis through mTOR signaling in mammary epithelial cells - Honghui Li (Nature Portfolio, 2017)
Abstract The MEN1 gene, which encodes the protein Menin, was investigated for its regulatory role in milk protein synthesis in mammary glands. Menin responds to nutrient and hormone levels via the PI3K/Akt/mTOR pathway. Bovine mammary epithelial cells and tissues were used as experimental models in this study. The results revealed that the milk protein synthesis capacity of mammary epithelial cells could be regulated by MEN1/Menin. The overexpression of Menin caused significant suppression of factors involved in the mTOR pathway, as well as milk protein κ-casein (CSNK). In contrast, a significant increase in these factors and CSNK was observed upon MEN1/Menin knockdown. The repression of MEN1/Menin on the mTOR pathway was also observed in mammary gland tissues. Additionally, MEN1/Menin was found to elicit a negative response on prolactin (PRL) and/or insulin (INS), which caused a similar downstream impact on mTOR pathway factors and milk proteins. Collectively, our data indicate that MEN1/Menin could play a regulatory role in milk protein synthesis through mTOR signaling in the mammary gland by mediating the effects of hormones and nutrient status. The discovery of Menin’s role in mammary glands suggests Menin could be potential new target for the improvement of milk performance and adjustment of lactation period of dairy cows.